2021
DOI: 10.1186/s12911-021-01561-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self-management in online health communities: an information exchange perspective

Abstract: Background Online health communities (OHCs), with a wealth of multi-source information exchange, have provided a convenient way for people with diabetes to actively participate in their self-management and have been widely used. Information exchange assists people with diabetes with health-related decisions to actively engage in their care, and reduce the occurrence of potential complications of diabetes. However, there has been relatively little research on the information exchange behaviors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This online exchange is also gradually shifting from a purely receptive to a two-way exchange of information, which enables patients to gain emotional and social support from interacting with users who share their experiences, leading them to derive more benefit from, and become more enthusiastic about, participating in online activities (34). According to a study conducted by Jin et al, health information shared by doctors or other self-glucose managers in China's largest online health community had an initiating and spreading effect, leading to the sugar users receiving the information becoming the dominant ones sharing the information and integrating themselves into the online internet (11). Increasing adherence to blood glucose management is aided by both faith in the Internet and the information exchange online, according to the results of another Chinese online poll (55).…”
Section: The Relationship Between Information Exchange and App Usage ...mentioning
confidence: 99%
See 2 more Smart Citations
“…This online exchange is also gradually shifting from a purely receptive to a two-way exchange of information, which enables patients to gain emotional and social support from interacting with users who share their experiences, leading them to derive more benefit from, and become more enthusiastic about, participating in online activities (34). According to a study conducted by Jin et al, health information shared by doctors or other self-glucose managers in China's largest online health community had an initiating and spreading effect, leading to the sugar users receiving the information becoming the dominant ones sharing the information and integrating themselves into the online internet (11). Increasing adherence to blood glucose management is aided by both faith in the Internet and the information exchange online, according to the results of another Chinese online poll (55).…”
Section: The Relationship Between Information Exchange and App Usage ...mentioning
confidence: 99%
“…Increasing adherence to blood glucose management is aided by both faith in the Internet and the information exchange online, according to the results of another Chinese online poll (55). Previous research has found a link between health literacy and effective blood glucose selfmanagement (11,56). In a randomized controlled trial of diabetes patients lasting 6 months, Zhang et al found a statistically significant drop in HbA1c of 2.03% in the app-interactive management group compared to 1.37% in the app-managed group, but no statistically significant difference in blood glucose self-monitoring (57), which means that information exchange is a potential factor in improving glycemic status and is a starting point for future research into glycemic control.…”
Section: The Relationship Between Information Exchange and App Usage ...mentioning
confidence: 99%
See 1 more Smart Citation
“…DKD may occur owing to multiple factors and is influenced by external environmental interactions, resulting in more complex self‐management. In the eHealth era, health devices provide a multifunction platform to assist patients in actively participating in disease care (Min et al, 2021). Patients with insufficient technical knowledge and skills may feel powerless and lack confidence and motivation in healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…They offer a virtual environment where people with a specific condition or needs can exchange information and experiences and interact with other people who share the same interest or condition, as well as getting support from peers and health professionals. [6][7][8] Online health communities might be particularly useful in supporting the self-management of chronic diseases and can therefore help to address some of the challenges in caring for people with chronic diseases. 9,10 Online health community users reportedly feel they have the "right knowledge to manage their illnesses" and increased empowerment through becoming better informed and receiving social support.…”
mentioning
confidence: 99%